(untitled) (Fiep Bulletin - online, 2019)
Introduction: The school is a privileged place for the implementation of public policies that promote the health ofchildren and adolescents through the incorporation of educational practices in health, such as actions to promote health and theinclusion of cross-cutting themes, as a daily school content. Objective: to analyze, in the view of the professional of physicaleducation, the theme education and health as a binomial in transversal themes in the teaching practice, in schools of urban areaof the public network of Campo Maior City - PI. Methodology: This is a field research, descriptive, with a qualitative approach. Theresearch was carried out with 08 Physical Education teachers who work in Fundamental Education I, in schools of the publicnetwork of Campo Maior - PI. As a data collection instrument, a semi-structured questionnaire. Results: The binomial Educationand health is seen with relevance by the teachers through the transversality, permeating a field of realities that in their totality is asearch of all, looking for the interdisciplinarity, respecting the levels of education, and related contents to health that do not werespecified. On the other hand, the precariousness for the development of the classes and the difficulty of dealing with the crosscuttingtheme in groups are particularly noteworthy. Conclusion: Thus, in the view of these professionals, it is concluded that theapproach to the subject has a certain basis, and contribute to the resolution that refers to the transversality of the health theme,where even so it is necessary a resourcefulness for the difficulties in which professionals they said facing.